A Practical Methodology for Forecasting the Impact of Changes in Influent Loads and Discharge Consents on Average Energy Consumption and Sludge Production by Activated Sludge Wastewater Treatment - Catarina Silva (MDPI AG, 2021)
This paper proposes a simple and easy-to-use methodology for forecasting the impact of changes in influent chemical oxygen demand (COD) and in the emission limit values (ELVs) of COD and total nitrogen on average energy requirements for aeration and sludge production by activated sludge wastewater treatment plants (WWTPs). The methodology is based on mass balances of sludge production and oxygen requirements for carbonaceous material biodegradation and/or nitrification, oxygen transfer and aeration equipment efficiency. Using average values of historical data of regular monitoring (water quality and operating conditions) WWTP-specific equations of oxygen requirements, energy consumption and sludge production are derived as a function of influent COD and influent N-total, which may be used to quantify the impact of influent and ELV changes. The methodology was tested in five extended aeration WWTPs for three scenarios established by the utility. The results show that increasing influent COD, from 900 to 1300 mg/L, for example, significantly increases the energy consumption by 49% and sludge production by 53%. For influent 54–68 mg/L N-total, imposing 15 mgN/L ELV results in a 9–26% increase in energy consumption. The COD ELV change studied (season-specific, from 150 mg/L 12 months/year to 125 mg/L 8 months/year to 100 mg/L 4 months/year) increases the energy consumption by 1.8–2.6% and the sludge production by 4.3–5.4%.